Ethnochemistry-based Adobe Flash Learning Media Using Indigenous Knowledge to Improve Students' Scientific Literacy - Heliawati, L.; Lidiawati, L.; Adriansyah, P. N. A.; Herlina, E. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This study aims to measure the effectiveness of using ethnochemistry-based Adobe Flash learning media using indigenous knowledge on scientific literacy. The study used a quasi-experimental method. The research subjects were 68 students who used ethnochemistry-based Adobe Flash learning media using indigenous knowledge on secondary metabolite material. The research is a quantitative study with pretest and posttest design. Data in the study were collected through tests to determine students' scientific literacy skills, including aspects of knowledge and competence in analyzing scientific phenomena, connecting chemical concepts to existing phenomena, and interpreting data or scientific evidence and questionnaires. Supporting data was obtained through a questionnaire to determine learning media users' opinions. The test was conducted with ten multiple-choice questions and a questionnaire with ten statements using a Likert scale of 1-4. The data analysis technique calculates the average score of test questions that have criteria according to scientific literacy and the percentage of user satisfaction. Based on the research results, the average value of 81.50 for scientific literacy skills on the concept of secondary metabolites with an N Gain of 80% is in a good category, and it is also known that the average percentage of user satisfaction is 83%, in a good category. Based on the hypothesis testing using the right-test, it has a t count of 16,160 and a t table of 2,021. The study concludes that applying ethnochemistry-based Adobe Flash learning media on secondary metabolites is effective for students' scientific literacy. Thus, it could be excluded that interactive media can support students' learning and improve scientific literacy.